Efficacy and Safety of Afatinib Plus Bevacizumab as First‐Line Treatment for Advanced NSCLC Patients With Epidermal Growth Factor Receptor (EGFR) Mutations: A Multicenter, Phase II Trial - Huiyang Shi; Miaohan Wang; Junling Li; Shi Jin; Minglei Zhuo; Jun Zhao; Hongxia Zhang; Meng Yang; Qingfang Shi; Haifeng Qin; Guilan Dong; Dongmei Lan; et al. (Thoracic Cancer)
ABSTRACT Background Studies indicated that afatinib combined with angiogenesis inhibitor may achieve promising efficacy in non‐small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations. Methods This is a multicenter, Phase II trial to explore the efficacy and safety of afatinib plus bevacizumab at first‐line setting for EGFR‐mutant NSCLC patients. The primary end point was progression‐free survival (PFS). The secondary end point included objective response rate (ORR), disease control rate (DCR) and safety. Results Between July 11, 2020 and November 11, 2021, 54 treatment‐naïve NSCLC patients were enrolled in the afatinib plus bevacizumab combination cohort. Meanwhile, 81 NSCLC patients with EGFR mutations treated with first‐line afatinib monotherapy were retrospectively collected. The median follow‐up time was 26.6 months. No significant difference in PFS was observed between the afatinib plus bevacizumab combination cohort and the afatinib monotherapy cohort (14.5 vs. 12.2 months, HR 0.87, p = 0.15), confirmed by propensity score matching (PSM) analysis. Patients with pleural metastasis (HR 0.56, 95% CI: 0.32–0.98, p < 0.05) and uncommon EGFR mutations (HR 0.61, 95% CI: 0.25–1.47, p = 0.05) experienced longer PFS in the combination cohort. ORR in the combination cohort is more favorable than in the afatinib monotherapy cohort (77.8% vs. 42.0%, p < 0.05). Diarrhea was the most common treatment‐related adverse events (TRAEs). 11.1% (6/54) patients had grade ≥ 3 TRAEs when treated with afatinib plus bevacizumab. Conclusion Afatinib combined with bevacizumab is well tolerated with moderate efficacy among patients with NSCLC, which might be a prospective strategy for patients with uncommon EGFR mutations and pleural metastasis. Trial Registration www.chictr.org.cn